HOW PUBLIC SERVICE LEADERSHIP IS STUDIED: AN EXAMINATION OF A QUARTER CENTURY OF SCHOLARSHIP. (8th August 2015) - CHAPMAN, CARRIE; GETHA‐TAYLOR, HEATHER; HOLMES, MAJA HUSAR; JACOBSON, WILLOW S.; MORSE, RICARDO S.; SOWA, JESSICA E.
Abstract : This exploratory study surveys the public service leadership literature from a selection of leading public administration journals over a 25‐year period (1987–2012). Patterns in methods used to study public leadership are explored, along with how those methods vary across settings within the public service sector and the treatment of leadership in the analysis. While the number of empirical studies of public service leadership has grown, the diversity of theoretical approaches, methods and measures challenges the ability to synthesize findings in order to advance the knowledge base on this topic. This article provides a map of leadership studies within the field of public administration over time and offers prescriptions for future research.